Current status and quantitative results of the AMYPAD prognostic and natural history study. (December 2021) - Gispert, Juan Domingo; Alves, Isadora Lopes; Gray, Katherine R.; Buckley, Christopher; Collij, Lyduine E.; Heeman, Fiona; Salvadó, Gemma; García, David Vállez; Connelly, Peter; Boutoleau‐Bretonnière, Claire; Pasquier, Florence; Dumurgier, Julien; et al.
Abstract: Background: Understanding the role of amyloid imaging in the earliest stages of Alzheimer's Disease (AD) becomes increasingly relevant for secondary prevention. In this context, the AMYPAD Prognostic and Natural History Study (PNHS) is an open‐label, prospective, multi‐centre cohort study (http://amypad.eu/ ) to determine the value of quantitative amyloid PET imaging in determining AD dementia risk. The study recruits from several European cohorts and aims at enrolling 2000 non‐demented individuals with a particular focus on those with emerging amyloid pathology. Method: As of January 25 th, 2020, AMYPAD PNHS had 17 actively recruiting sites across Europe, and 782 non‐demented participants (>95% cognitively unimpaired) had consented to participate in the study. Of those, 448 are from EPAD LCS, 129 from EMIF‐AD Twin 60++, 111 from FACEHBI, 70 from ALFA+, 17 from FPACK, and 7 from the UCL‐2010‐412 cohort. Of the consented subjects, 334 already had an amyloid PET scan before this study. Within AMYPAD PNHS, 588 subjects have hitherto been scanned with either [ 18 F]flutemetamol or [ 18 F]florbetaben. Of note, 53.6% of the total number of scans have been acquired with a dual‐time window dynamic protocol. The primary outcome measure is the Centiloid value (CL) using the whole cerebellum as reference region, to enable quantitative comparability between the two tracers in the study. Also, images have been visually assessed by local raters. Of the 588 acquired scans, 296 have been quantified with IXICO's LEAP pipeline and passed Quality Control, thus rendering valid CL values. Subjects were categorized as amyloid‐negative (CL≤12); as in a "gray‐zone" (1250) and a Gaussian Mixture Model was used to assess the population's Centiloid distribution. Result: Based on visual assessment, 28% of the fully 296 quantified scans were visually rated as positive and 72% as negative. Quantitatively, 50% of them were categorized as negative, 33% in the gray‐zone, and 17% were positive (Figure 1). Centiloid values ranged from ‐30.3 to 154.2 (Mean±SD: 22.5±32.0 CL) (Figure 2). Conclusion: Preliminary quantitative results indicate that PNHS is being successful in recruiting a cohort mostly composed of cognitively unimpaired individuals who are enriched for early amyloid abnormalities, which is the intended target population.